L’imaginaire apocalyptique et son réinvestissement dans Battlestar Galactica de Ronald D. Moore: du piège des prophéties à la quête de liberté - Marie-Lucie Bougon (TV Series, 2017)
This article explores how Ronald D. Moore’s Battlestar Galactica reinvents and resolutely updates apocalyptic patterns, and analyzes how the show wavers between the fascination for the oracular and the constant search for emancipation. First we will review the multiple Biblical references and examine how the show updates them; then we will look into the proliferation of messianic figures. Finally, we will study the conclusion of the narrative, which moves towards the denial of all prophecies.